Efficient automated syntheses of high specific activity 6‐[18F]fluorodopamine using a diaryliodonium salt precursor1. (23rd December 2015) - Neumann, Kiel D.; Qin, Linlin; Vāvere, Amy L.; Shen, Bin; Miao, Zheng; Chin, Frederick T.; Shulkin, Barry L.; Snyder, Scott E.; DiMagno, Stephen G.
Abstract : 6‐[ 18 F]Fluorodopamine (6‐[ 18 F]F‐DA) is a positron emission tomography radiopharmaceutical used to image sympathetic cardiac innervation and neuroendocrine tumors. Imaging with 6‐[ 18 F]F‐DA is constrained, in part, by the bioactivity and neurotoxicity of 6‐[ 19 F]fluorodopamine. Furthermore, routine access to this radiotracer is limited by the inherent difficulty of incorporation of [ 18 F]fluoride into electron‐rich aromatic substrates. We describe the simple and direct preparation of high specific activity (SA) 6‐[ 18 F]F‐DA from no‐carrier‐added (n.c.a.) [ 18 F]fluoride. Incorporation of n.c.a. [ 18 F]fluoride into a diaryliodonium salt precursor was achieved in 50–75% radiochemical yields (decay corrected to end of bombardment). Synthesis of 6‐[ 18 F]F‐DA on the IBA Synthera® and GE TRACERlab FX‐FN automated platforms gave 6‐[ 18 F]F‐DA in >99% chemical and radiochemical purities after HPLC purification. The final non‐corrected yields of 6‐[ 18 F]F‐DA were 25 ± 4% ( n = 4, 65 min) and 31 ± 6% ( n = 3, 75 min) using the Synthera and TRACERlab modules, respectively. Efficient access to high SA 6‐[ 18 F]F‐DA from a diaryliodonium salt precursor and n.c.a. [ 18 F]fluoride is provided by a relatively subtle change in reaction conditions – replacement of a polar aprotic solvent (acetonitrile) with a relatively nonpolar solvent (toluene) during the critical radiofluorination reaction. Implementation of this process on common radiochemistry platforms should make 6‐[ 18 F]F‐DA readily available to the wider imaging community. Abstract : 6‐[ 18 F]Fluorodopamine (6‐[ 18 F]F‐DA) is a positron emission tomography radiopharmaceutical used to image sympathetic cardiac innervation and neuroendocrine tumors. Imaging with 6‐[ 18 F]F‐DA is limited by the difficulty of late‐stage incorporation of [ 18 F]fluoride into electron‐rich aromatic substrates. We report that the fully automated synthesis of 6‐[ 18 F]F‐DA on the IBA Synthera® and GE TRACERlab FX‐FN automated platforms in non‐corrected yields of [ 18 F]F‐DA was 25 ± 4% ( n = 4; 65 min) and 31 ± 6% ( n = 3; 75 min) using the Synthera and TRACERlab modules, respectively.